Prospects for the development of Kazakhstan's currency market (Journal of Economic Research & Business Administration, 2015)
"In the clause are considered main prospects of development of the exchange market for the purpose of stable economy. Effective tools for realization of development of the exchange market and their subsequent introduction in practical application are resulted. "
Keywords: The foreign exchange market; devaluation